Efficacy and safety of chimeric antigen receptor T cell therapy in relapsed/refractory diffuse large B-cell lymphoma with different HBV status: a retrospective study from a single center - Kong, Danqing; Ping, Nana; Gao, Xin; Zou, Rui; Wang, Peng; Wu, Depei; Jin, Zhengming; Qu, Changju (Frontiers in Immunology, 2023)
Background Chimeric antigen receptor T cell (CAR-T) therapy is an effective salvage treatment in relapsed or refractory(r/r) diffuse large B-cell lymphoma (DLBCL), but the impact of hepatitis B virus (HBV) infection has not been studied. Methods and results Here, 51 patients with r/r DLBCL receiving CAR-T therapy were enrolled and analyzed at the First Affiliated Hospital of Soochow University. The overall response rate and the complete remission rate (CR) of CAR-T therapy were 74.5% and 39.2%, respectively. With a median follow-up of 21.1 months after CAR-T, the probabilities of overall survival (OS) and progression-free survival (PFS) at 36 months were 43.4% and 28.7%, respectively. These patients were divided into three cohorts including chronic HBV infection group (n=6), resolved HBV infection group (n=25) and non-HBV infection group (n=20). Bone marrow involvement was significantly higher in the HBV infection group(P<0.001), other basic characteristics before CAR-T therapy were comparable. Subgroup analysis showed that HBV infection status did not affect the efficacy of CAR-T therapy in CR rate, OS or PFS, and there was no significant difference in CAR-T related toxicities between three cohorts. Only one cirrhosis patient with chronic HBV infection experienced HBV reactivation. Conclusions CAR-T therapy was effective and can be used safely in r/r DLBCL with HBV infection under proper monitoring and antiviral prophylaxis.